Emerging markets and e-commerce in developing economies - Rouibah, Kamel; Khalil, Omar; Hassanien, Aboul Ella 1964- (Premier reference source, 2009)
"This book provides researchers readers with a synthesis of current research on developing countries experience with e-commerce" - Provided by publisher